Peranan Badan Pengawas Obat Dan Makanan Dalam Memberikan Perlindungan Studi Di Kantor Cabang Badan Pengawas Obat Dan Makanan Badan Pengawas Obat Makanan (BPOM) Tanjungbalai - Bahmid Bahmid; Junindra Martua; Arbiah Arbiah (Universitas Muhammadiyah Sumatera Utara, 2020)
The Food Medicine Supervisory Agency (BPOM) has a duty under health minister which responsible directly to President. The lack of application of food standards made by BPOM principally as the one on BPOMs task relating drug and food supervision in Indonesia. Medicines and foods consist of drugs, drug ingredients, narcotics, psychotropic substances, precursors, addictive substances, traditional medicines, health supplements, cosmetics, and processed foods. BPOM is under Presidential Regulation Number 80 Year 2017 concerning BPOM. The authors of this writing use empirical juridical legal research methods deductively and inductively. The authors examined about BPOM's efforts in Drug and Food Control in Tanjungbalai City regarding BPOM's authority in performing consumer protection in Tanjungbalai City. Based on the formulation of the problem, the authors can conclude that BPOM in Tanjungbalai has performed its duties and authority as the food and drug supervisory agency under applicable regulations and there is legal protection for consumers who feel disadvantaged against all types of products that have passed by BPOM through the court or outside the court.